2018
DOI: 10.3390/cancers10080270
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Mutational Status of NSCLC Using Hypermetabolic Circulating Tumor Cells

Abstract: Molecular characterization is currently a key step in NSCLC therapy selection. Circulating tumor cells (CTC) are excellent candidates for downstream analysis, but technology is still lagging behind. In this work, we show that the mutational status of NSCLC can be assessed on hypermetabolic CTC, detected by their increased glucose uptake. We validated the method in 30 Stage IV NSCLC patients: peripheral blood samples were incubated with a fluorescent glucose analog (2-NBDG) and analyzed by flow cytometry. Cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…2-NBDG) for a short time and then be evaluated using fluorescence microscopy. Turetta et al have shown that glucose uptake values of CTCs are a median of 10 times higher than those of white blood cells (44).…”
Section: Morphology and Biological Features Morphological Evaluationmentioning
confidence: 99%
“…2-NBDG) for a short time and then be evaluated using fluorescence microscopy. Turetta et al have shown that glucose uptake values of CTCs are a median of 10 times higher than those of white blood cells (44).…”
Section: Morphology and Biological Features Morphological Evaluationmentioning
confidence: 99%
“…A plethora of new technologies emerged to overcome the limitations of EpCAM-based approaches, focusing on the challenge of detecting non-epithelial CTCs, mainly exploiting mesenchymal markers or physical features of cancer cells and other cancer-specific traits. Notably, few groups have specifically addressed altered metabolism of cancer cells [22][23][24][25][26][27]-recognized as a "hallmark of cancer" [28]-as a promising approach, also in view of the introduction of specific metabolic agent combined with chemo-or immunotherapies in several clinical trials [29][30][31]. One of the most described metabolic alterations of cancer cells consists of a markedly increased uptake of glucose in comparison with normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…First described by Otto Warburg in the 1920s, this cancer feature has been successfully exploited in the clinic by introducing a positron emission tomography (PET)-based imaging of the uptake of a radioactive glucose analog, which is commonly employed to stage cancer and assess response to therapy [32]. Several groups reported the exploitation of metabolic alterations to identify CTCs in the peripheral blood of metastatic cancer patients, independently from EpCAM expression and immunostaining techniques in general [22][23][24][25][26][27]. An mRNAseq study on CTCs from prostate cancer patients described a category of CTCs with an upregulation of metabolic transcripts as a potential biomarker for cancer metastasis [24].…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of new technologies emerged to overcome the limitations of EpCAM-based approaches, focusing on the challenge of detecting non-epithelial CTCs, mainly exploiting mesenchymal markers or physical features of cancer cells and other cancer-specific traits. Notably, few groups have specifically addressed altered metabolism of cancer cells (22)(23)(24)(25)(26)(27) recognized as a "hallmark of cancer"(28) -as a promising approach, also in view of the introduction of specific metabolic agent combined with chemo-or immunotherapies in several clinical trials (29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…First described by Otto Warburg in the 1920s, this cancer feature has been successfully exploited in the clinic by introducing a positron emission tomography (PET)-based imaging of the uptake of a radioactive glucose analog, which is commonly employed to stage cancer and assess response to therapy (32). Several groups reported the exploitation of metabolic alterations to identify CTCs in the peripheral blood of metastatic cancer patients, independently from EpCAM expression and immunostaining techniques in general (22)(23)(24)(25)(26)(27). An mRNAseq study on CTCs from prostate cancer patients described a category of CTCs with an upregulation of metabolic transcripts as a potential biomarkers for cancer metastasis (24).…”
Section: Introductionmentioning
confidence: 99%